AN An Analysis of Parent’s and Communities' Awareness of The Importance of Developing Multiple Intelligences in Early Childhood - Haris, Fakhita Indira (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Parents and society often demand that children master predetermined skills. This condition certainly hinders children's development. The method used in this research is Systematic Literature Review. The data used are taken from relevant journals, books and articles within 10 years. Then the data is analyzed and compiled so as to conclude the discussion with the keywords of parental and community awareness, multiple intelligences, and early childhood. The results show that Lack of awareness can have a negative impact on children's development, such as limited exploration of potential, low self-confidence, and difficulties in social and emotional development. Conversely, high awareness can encourage children to develop holistically, increase creativity, independence, and readiness to face future challenges. To increase parental awareness, various strategies are needed, such as parenting education and training, collaboration between parents and educational institutions, utilization of digital media, and strengthening parenting communities. With a systematic and sustainable approach, parents' awareness of multiple intelligences can be increased, thereby supporting more optimal child development in various aspects of life